2016
DOI: 10.3390/ijms17040466
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Apoptotic and Pro-Survival Effect of Alpinate Oxyphyllae Fructus (AOF) in a d-Galactose-Induced Aging Heart

Abstract: Aging, a natural biological/physiological phenomenon, is accelerated by reactive oxygen species (ROS) accumulation and identified by a progressive decrease in physiological function. Several studies have shown a positive relationship between aging and chronic heart failure (HF). Cardiac apoptosis was found in age-related diseases. We used a traditional Chinese medicine, Alpinate Oxyphyllae Fructus (AOF), to evaluate its effect on cardiac anti-apoptosis and pro-survival. Male eight-week-old Sprague–Dawley (SD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 121 publications
(133 reference statements)
0
45
0
Order By: Relevance
“…In that study, Kunming mice at the age of 4–6 weeks old were used. Compared to this, the initial age of the rats and mice in other studies was 8–20 weeks old . Therefore, the differing findings could be explained by the fact that the starting age of experimental animals is the key determinant to create an effective d ‐galactose‐induced ageing model.…”
Section: Effects Of D‐galactose Administration On Cardiac Oxidative Smentioning
confidence: 83%
See 3 more Smart Citations
“…In that study, Kunming mice at the age of 4–6 weeks old were used. Compared to this, the initial age of the rats and mice in other studies was 8–20 weeks old . Therefore, the differing findings could be explained by the fact that the starting age of experimental animals is the key determinant to create an effective d ‐galactose‐induced ageing model.…”
Section: Effects Of D‐galactose Administration On Cardiac Oxidative Smentioning
confidence: 83%
“…The mechanisms of how d ‐galactose induced an ageing heart can be identified, according to this review, include those resulting in increased oxidative stress and reduced levels of antioxidants , increased apoptosis , an alteration in calcium homeostasis and impaired cardiac morphology . These mechanisms, separately or severally, lead ultimately to cardiac dysfunction . These pathways may be targets for developing strategies for approaching the issues associated with anti‐ageing in the future.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, SIRT1 inhibits NF‐κB mediated transcriptional activations via direct interaction with the NF‐κB p65 subunit at lysine 310 (Yeung et al, ). Our previous study demonstrated that SIRT1 is markedly reduced in aging rat hearts; however, AOF treatment reverts the levels of SIRT1 and promotes PGC‐1α activation (Chang et al, ).…”
Section: Discussionmentioning
confidence: 98%